ETNOMATEMATIKA: KARAKTERISTIK BATIK BONDOWOSO DI RUMAH PRODUKSI KI RONGGO - Yudianto, Erfan; Susanto, Susanto; Setiawan, Toto' Bara; Diyanah, Hidayatud (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
AbstractEthnomatematics is the connection between mathematics and culture. This research aimss to describe the ethnomathematics of Batik Bondowoso. This study used qualitative researchÂ  with an ethnographic approach. The subjects are 3 craftsmen at Batik Kironggo house production. Data were collected by using observation, interview, and documentation. The result of this study indicates the existence of ethnomathematics at Bondowoso batik that is concepts or elements found, such as: points, lines, angles, 2D shapes (square, rhombus and circles), similarities and geometric transformations (translation, reflection, rotation and dilatation).Â Keywords: Batik of Bondowoso, Ethnomathematics; Geometry.